ChemInform Abstract: Copper‐Mediated ortho C—H Sulfonylation of Benzoic Acid Derivatives with Sodium Sulfinates. Issue 32 (August 2015) - Liu, Jidan; Yu, Lin; Zhuang, Shaobo; Gui, Qingwen; Chen, Xiang; Wang, Wenduo; Tan, Ze
Abstract A novel copper‐mediated auxiliary‐assisted ortho C—H bond sulfonylation of the benzoic acid derivative with a variety of sodium sulfinates is reported.